2019
DOI: 10.1039/c9ra07743j
|View full text |Cite
|
Sign up to set email alerts
|

Modified melamine-formaldehyde resins improve tensile strength along with antifouling and flame retardancy in impregnation of cellulose paper

Abstract: Polyvinyl alcohol (PVA) and benzoguanamine (BG) modified melamine-formaldehyde (MF) resins were used to prepare high-pressure laminates (HPLs) and the improved tensile strength, flame retardancy and antifouling properties were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…It is also found that the tensile strength of the modified UF is higher at 2 wt% PVA loading and then decreases with increasing PVA content. Similar trend of tensile strength was observed in modified melamine formaldehyde resin and modified epoxy resin [31][32]. The addition of PVA improved the tensile strength performance of the PVA modified UF resin due to the form of physical crosslinking between the resin with flexible chain of PVA, so PVA shared part of the stress uniformly when subjected to external forces that increased the tensile strength of modified resin.…”
Section: Mechanical Properties Of Uf and Pva Modified Uf Resinsupporting
confidence: 70%
“…It is also found that the tensile strength of the modified UF is higher at 2 wt% PVA loading and then decreases with increasing PVA content. Similar trend of tensile strength was observed in modified melamine formaldehyde resin and modified epoxy resin [31][32]. The addition of PVA improved the tensile strength performance of the PVA modified UF resin due to the form of physical crosslinking between the resin with flexible chain of PVA, so PVA shared part of the stress uniformly when subjected to external forces that increased the tensile strength of modified resin.…”
Section: Mechanical Properties Of Uf and Pva Modified Uf Resinsupporting
confidence: 70%
“…That is attributed to interaction between functional groups of soy protein and that of the MF and cellulose of jute. 10,12 A plausible mechanism of synergic bonding between functional groups of cellulose, soy protein and melamine formaldehyde are given in Figure 3. Increase in MF content from 0 to 50 wt.%, also enhanced flexural strength from 33.54 (MMSJ1) to 64.8 MPa (MMSJ6) and flexural modulus from 1219 MPa to 5821 MPa.…”
Section: Mechanical Strength Of Compositesmentioning
confidence: 99%
“…groups of leather samples, which each group have 15 pieces (140 mm x 60 mm) that were taken from flameretardant leather were tested in parallel in a limiting oxygen index chamber according to ASTM D 2863-77 LOI test [14]. For SEM analysis the samples were placed on a scanning electron microscope (Fei-Quanta Feg 250) and their images were taken at 500 µm and 100 µm magnifications.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…[13]. When the flame retardancy effects of resins in different materials are examined in the literature; Chen et al, used modified melamine resins on cellulose papers because it is a thermoset resin and they found that LOI values of papers were increased from 32% to 33.5% by the effect of melamine resin [14]. Gaan et al benefited from nitrogen phosphorus synergistic effect to increase flame retardancy property of TBP in cotton fibers and they used nitrogen containing urea and melamine resins.…”
Section: Introductionmentioning
confidence: 99%